2017
DOI: 10.1002/2017ja024553
|View full text |Cite
|
Sign up to set email alerts
|

Energy budget and mechanisms of cold ion heating in asymmetric magnetic reconnection

Abstract: Cold ions (few tens of eV) of ionospheric origin are commonly observed on the magnetospheric side of the Earth's dayside magnetopause. As a result, they can participate in magnetic reconnection, changing locally the reconnection rate and being accelerated and heated. We present four events where cold ion heating was observed by the Magnetospheric Multiscale mission, associated with the magnetospheric Hall E field region of magnetic reconnection. For two of the events the cold ion density was small compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 69 publications
8
39
1
Order By: Relevance
“…These oscillations at the lower‐hybrid frequency (∼15 Hz) cannot be resolved by the FPI ion time resolution (150 ms). The waves propagate along the − M direction, which is similar to lower‐hybrid waves driven by interaction between cold and hot ions that have been observed at the magnetopause (Graham et al, ), suggested as a mechanism for heating cold ions (Toledo‐Redondo et al, ). Around 17:57:12.1 UT MMS observed a j M current sheet with a peak current of 180 nA/m 2 and a thickness of ∼24 km (∼1.8 ρ ce ), denoted by the first vertical line in Figure .…”
Section: Observationssupporting
confidence: 56%
“…These oscillations at the lower‐hybrid frequency (∼15 Hz) cannot be resolved by the FPI ion time resolution (150 ms). The waves propagate along the − M direction, which is similar to lower‐hybrid waves driven by interaction between cold and hot ions that have been observed at the magnetopause (Graham et al, ), suggested as a mechanism for heating cold ions (Toledo‐Redondo et al, ). Around 17:57:12.1 UT MMS observed a j M current sheet with a peak current of 180 nA/m 2 and a thickness of ∼24 km (∼1.8 ρ ce ), denoted by the first vertical line in Figure .…”
Section: Observationssupporting
confidence: 56%
“…The aim of the present section is to report on the statistical analysis of individual energy spectra in a large‐scale fashion, to determine their spatial distribution, occurrence, and how they are ordered by interplanetary conditions (IMF). It should be noted that the magnetosphere also contains even colder ions of ionospheric origin (André & Cully, ; Chappell et al, ; Sauvaud et al, ), but once inside the LLBL they are heated and mostly indistinguishable from ions of magnetosheath origin (Dargent et al, ; Toledo‐Redondo et al, , ). They are thus not addressed in the present study.…”
Section: Statistics Of Multiple Ion and Electron Populationsmentioning
confidence: 99%
“…Cold ions are heated and accelerated in the separatrix region (Divin et al, ; Toledo‐Redondo, André, Vaivads, et al,; Toledo‐Redondo et al, , ). Once in the exhaust, they mix with magnetosheath ions and, therefore, become hard to distinguish from other ions in spacecraft data (André et al, ; Li et al, ; Toledo‐Redondo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this heating, cold ions take part in the energy budget of magnetic reconnection (Aunai et al, ) in some yet unknown proportion. A recent study based on four independent observations by MMS of the reconnecting magnetopause with cold ions showed that cold ions take at least 10–25% of the energy spent into particle heating (Toledo‐Redondo et al, ). To study cold ion heating, numerical simulations have the advantage of being able to flag ions and then discriminate cold ions from other populations, even once heated.…”
Section: Introductionmentioning
confidence: 99%